A gap in the Pliocene invasion of seawater to the Gulf of California - Jorge Ledesma-Vázquez (Revista Mexicana de Ciencias Geológicas)
The Proto-Gulf extensional province was formed during the Miocene, from 14 to 12 Ma. During the main extensional period, within the Baja California central domain, several depocenters were formed including the El Boleo basin, followed to the south by the Bahía Concepción basin, and to the southeast, the San Nicolás basin. The San Nicolás basin is associated with the transfer zone coupled to the Bahía Concepción accommodation zone. The Miocene extensional process resulted in the uplift and exhumation of the regional Cretaceous granodiorite basement in the Concepción peninsula, Punta San Antonio, and San Juan Londó valley. The episode of extension is responsible for the tilting of volcanic blocks of Miocene age. The late Pliocene San Nicolás Formation is a lithostratigraphic unit with three sedimentary members. Most of the sedimentary units in the San Nicolás Formation reflect a post-extensional episode that involved rapid initial subsidence, reactivation associated with low rates of sedimentation, followed by periods of shallow water deposition dominated by storm activity, and the presence of large scale sand wave deposits which delineate extreme tidal conditions. The maximum age assigned to the San Nicolás Formation is 3.3 ± 0.5 Ma.  In contrast, at Punta Chivato, and in the Bahía Concepción area, all the marine units are assigned to the lower Pliocene San Marcos Formation, and upper Pliocene Marquer Formation. Here, the marine strata reflect a post-extensional episode that involved low rates of subsidence, associated with moderate rates of sedimentation followed by periods of shallow water deposition dominated by very low energy. These relationships suggest that during the late Pliocene, the interconnection between the Proto-Gulf and the Gulf of California was not completed, and the head of the developing modern Gulf of California was near the San Nicolás basin during the late Pliocene, clearly associated with the transtensional regime responsible for the present tectonic configuration in the Gulf of California.